Stem-Integrated Project-Based Learning With Flipbook Media to Enhance Science Process Skills and Learning Outcomes - Sutanto; Mohammad Masykuri; Sukarmin (Jurnal PAJAR (Pendidikan dan Pengajaran), 2026)
The integration of STEM education and Project-Based Learning (PjBL) has been widely acknowledged as a practical approach to developing students' scientific competencies. However, empirical findings remain fragmented, particularly regarding the impact of flipbook media on science process skills and learning outcomes. This study aims to systematically review current research on the integration of STEM-based PjBL in science education. A Systematic Literature Review (SLR) was conducted using the PRISMA protocol. Articles were retrieved from Scopus, Google Scholar, and SINTA databases, yielding 45 studies published between 2020 and 2024. Based on predefined inclusion and exclusion criteria related to relevance, accessibility, and methodological rigor, 15 studies were selected for in-depth analysis. The findings indicate that STEM-integrated PjBL contributes significantly to the development of science process skills, particularly in observation, experimentation, data interpretation, and problem-solving. Several studies also report improvements in students' conceptual understanding and learning outcomes, particularly when flipbook media are used to enhance engagement and structured learning support. Nonetheless, challenges were identified, including students' readiness for project-based tasks and the need for sustained teacher scaffolding. In conclusion, STEM-integrated PjBL supported by flipbook media is a pedagogically robust approach to strengthening science learning. Future studies are recommended to employ more rigorous designs to improve generalizability.